2013
DOI: 10.1504/ijsmile.2013.051650
|View full text |Cite
|
Sign up to set email alerts
|

Social media and higher education: introversion and collaborative learning from the student's perspective

Abstract: The aim of this study is to understand how social media contribute to face-to-face collaborative learning by introvert students in higher education. A total of 233 students participated. This study shows that more introvert students perceive that social media are more helpful for increasing their collaborative learning performance and self-confidence. These students feel that their true nature is hampered in face-to-face contact and prefer to communicate via social media rather than face-to-face communication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…How and Why Educators Use Twitter instructors (Chen & Chen, 2012), boosting collaborative learning and self-confidence among introverted students (Voorn & Kommers, 2013), and encouraging informal learning outside the classroom (Dunlap & Lowenthal, 2010;Kassens-Noor, 2012). Research suggests Twitter has the potential to encourage concise writing (e.g., Dunlap &Lowenthal, 2009), andKurtz (2009) further found that his elementary students were excited to co-construct tweets and analyze language appropriate for the authentic audience of their family members.…”
Section: Class Activitiesmentioning
confidence: 99%
“…How and Why Educators Use Twitter instructors (Chen & Chen, 2012), boosting collaborative learning and self-confidence among introverted students (Voorn & Kommers, 2013), and encouraging informal learning outside the classroom (Dunlap & Lowenthal, 2010;Kassens-Noor, 2012). Research suggests Twitter has the potential to encourage concise writing (e.g., Dunlap &Lowenthal, 2009), andKurtz (2009) further found that his elementary students were excited to co-construct tweets and analyze language appropriate for the authentic audience of their family members.…”
Section: Class Activitiesmentioning
confidence: 99%
“…The potential of wiki as a knowledge construction tool through collaboration with peers is well supported by the literature (Brown 2012 ;Coutinho and Bottentuit 2007 ;Hew and Cheung 2010 ;Voorn and Kommers 2013 ). The potential of wiki as a knowledge construction tool through collaboration with peers is well supported by the literature (Brown 2012 ;Coutinho and Bottentuit 2007 ;Hew and Cheung 2010 ;Voorn and Kommers 2013 ).…”
Section: Peers' Infl Uences and Wiki-based Learningmentioning
confidence: 88%
“…This finding may imply that in the face-to-face learning condition, extroverts directed more resources to social activities (Blau and Barak 2009a;Voorn and Kommers 2013), resulting in the acquisition of less literal knowledge, while introverts were more focused on learning. In contrast, in the online learning conditions, which are associated with less social distractions (Kock, Verville, and Garza 2007), the extroverts could exercise their learning advantages.…”
Section: Discussionmentioning
confidence: 99%
“…According to this principle, while extroverts feel comfortable in both online and offline conditions, introverts tend to feel more comfortable in online environments (McKenna et al 2007), where they may even adopt extroverted behaviours. While the research literature does not report differences in introverts' and extroverts' academic achievements, introverts have been found to invest more time studying, whereas extroverts tend to spend more time socialising, both offline and online (Blau and Barak 2009a;Voorn and Kommers 2013). Furthermore, although introverts have ideas that may contribute to learning, they often feel uncomfortable expressing them in the face-to-face classroom setting (Blau and Barak 2012).…”
Section: Face-to-face Learningmentioning
confidence: 99%